2020
DOI: 10.1038/s41467-020-19042-y
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of hPSC-derived pericyte-like cells promotes functional recovery in ischemic stroke mice

Abstract: Pericytes play essential roles in blood–brain barrier (BBB) integrity and dysfunction or degeneration of pericytes is implicated in a set of neurological disorders although the underlying mechanism remains largely unknown. However, the scarcity of material sources hinders the application of BBB models in vitro for pathophysiological studies. Additionally, whether pericytes can be used to treat neurological disorders remains to be elucidated. Here, we generate pericyte-like cells (PCs) from human pluripotent st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 62 publications
2
80
0
Order By: Relevance
“…Pericytes have been shown to acquire properties similar to stem cells and microglia after cerebral ischemia, providing another potential therapeutic strategy for recovery from ischemic stroke ( Özen et al, 2014 ; Nakagomi et al, 2015 ). Recently, Sun J. et al (2020) generated pericyte-like cells (PCs) from human pluripotent stem cells (hPSCs). They found the cranial neural crest-derived pericyte-like cells (hPSC-CNC PCs) expressed typical pericyte markers and showed distinct pericyte properties.…”
Section: Introductionmentioning
confidence: 99%
“…Pericytes have been shown to acquire properties similar to stem cells and microglia after cerebral ischemia, providing another potential therapeutic strategy for recovery from ischemic stroke ( Özen et al, 2014 ; Nakagomi et al, 2015 ). Recently, Sun J. et al (2020) generated pericyte-like cells (PCs) from human pluripotent stem cells (hPSCs). They found the cranial neural crest-derived pericyte-like cells (hPSC-CNC PCs) expressed typical pericyte markers and showed distinct pericyte properties.…”
Section: Introductionmentioning
confidence: 99%
“…The blood-brain barrier (BBB) is disrupted after a stroke. The transplanted stem cells can easily cross the BBB to gather in the infarcted brain areas and reconstruct the BBB integrity (Bang et al, 2017 ; Sun et al, 2020 ). Those cells can differentiate into various types of cells forming nervous tissue (e.g., mature neurons, oligodendrocytes, and astrocytes) and release a host of neurotrophic factors and cytokines [e.g., vascular endothelial growth factor (VEGF), brain-derived neurotrophic factor (BDNF), basic fibroblast growth factor (bFGF), nerve growth factor (NGF), insulin-like growth factor 1 (IGF-1)], which could promote neurogenesis to replace injured cells and improve neurological function (Ishibashi et al, 2004 ; Schinköthe et al, 2008 ; Kupcova Skalnikova, 2013 ).…”
Section: Potential Mechanisms Of Stem Cell Therapy For Ischemic Strokmentioning
confidence: 99%
“…Several studies have suggested that a reduction in apoptosis in the ischemic boundary area occurs following cellular therapy that is associated with improved neurological recovery in experimental models (Stonesifer et al, 2017 ; Sun et al, 2020 ). It was reported that the neuroprotective effects of human bone marrow mesenchymal stem cells (hMSCs) against cerebral ischemia could be antagonized by the apoptosis-related Bcl-2 antibody (Zhang et al, 2019 ).…”
Section: Potential Mechanisms Of Stem Cell Therapy For Ischemic Strokmentioning
confidence: 99%
See 1 more Smart Citation
“…Mature pericytes then become LCBF regulators and by regulating the diameter of capillary vessels and the metabolic and Ca 2+ signals, actively involve the capillary vascular tone ( Cai et al, 2018 ). Pericyte of both endogenous and exogenous sources may interact with NSC or co-transplanted cells to promote flow recovery ( Sun et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%